Electrical study of impurity states in conjugated polymers - Stallinga, Peter (2015)
Schottky diodes resulting from an intimate contact of aluminum on electro-deposited poly(3-methylthiopene), PMeT, have been studied by admittance spectroscopy, capacitance-voltage and current-voltage measurements, and optically-induced current transients. The loss-tangents show the existence of interface states that can be removed by vacuum annealing, also visible in the transients. Furthermore, the CV curves don't substantiate the idea of movement of the dopant ions.